Upholding human dignity in AI: Advocating moral reasoning over consensus ethics for value alignment - Octavian-Mihai Machidon (Zagadnienia Filozoficzne w Nauce)
Artificial intelligence (AI) offers transformative advancements across sectors such as healthcare, agriculture, and environmental sustainability. However, a pressing ethical challenge remains: aligning AI systems with human values in a manner that is stable, coherent, and universally applicable. As AI increasingly mediates human perception, shapes social interactions, and influences decision-making, it raises profound ethical concerns about its impact on human dignity and social well-being. The prevailing consensus-based approach, advocated by figures such as Google DeepMind’s Iason Gabriel, suggests that AI ethics should reflect majority societal or political viewpoints. While this model offers flexibility, it also risks moral relativism and ethical instability as social norms fluctuate. This paper argues that consensus-based ethics are inadequate for safeguarding fundamental values—especially human dignity—which should not be subject to shifting public opinion. Instead, it advocates for a moral framework that transcends cultural and political trends, providing a stable foundation for AI ethics. Through case studies like social media recommendation algorithms that exploit users’ vulnerabilities, particularly those of children and teenagers, the paper highlights the risks of AI systems driven by profit-oriented metrics without ethical oversight. Drawing on insights from moral philosophy and theology, particularly the works of Joseph Ratzinger, it contends that aligning AI with moral reasoning is essential to uphold human dignity, prevent texploitation, and promote the common good.